Study on Mechanical Properties of Concrete Containing Rubber Fine Aggregate as a Replacement Material in Concrete Mix - Puteri Me Aleeyana; Mohamad Luthfi; Muhammad Hairi Osman (Progress in Engineering Application and Technology, 2024)
This research involved the production of Rubber waste material as a replacement material for natural fine aggregates in the concrete mix. The first objectives of this study were to determine the compressive strength and density of concrete containing Rubber Fine Aggregate(RFA). The second objective is to evaluate the effectiveness of Rubber Fine Aggregate (RFA) needed as replacement materials in concrete mix. Due to the disposal of waste tires which had problems because tires do not biodegrade landfill sites become overcrowded and the prices of natural aggregate begin to increase due to the limited resources. This research was made to reduce of dependence on raw materials and reduce pollution caused by the waste of tires. In methodology, the waste tires were cut into smaller pieces during the shredding process. The design of the concrete mix was calculated using the Design of Normal Concrete Mix and the percentage of concrete containing RFA was set at 0%, 3%, 6%, and 9%. Compressive strength and density test will be conducted where 24 concrete cubes were tested at the age 7 and 28 days after curing process. Based on data analysis and result shows that 3% of the percentage containing Rubber Fine Aggregate gives minimum density and maximum compressive strength compared with 6% and 9%. However, objective of this research not achieve because there have two error which are wrong type of cement and calculation of design of the concrete mix during material preparation.